Veje og vad fra neolitikum til middelalder ved Kastbjerg Å i Østjylland - Madsen, Bo (Kuml, 2025)
Ancient causeways by Kastbjerg Å in East Jutland A river valley rehabilitation project undertaken by the Danish Nature Agency in East Jutland involved re-meandering and regulation of the river Kastbjerg Å (figs. 1-3). In the bog at Enslev in the central river valley, the re-establishment of a large meander, Curve 2, on the southern side of the valley, along the old parish boundary, led to a decrease in groundwater levels of more than 2 m and substantial drainage of the peat. A survey revealed that several prehistoric trackways had been cut through during these works. Rescue excavations conducted during three campaigns by Museum Østjylland revealed a group of at least 14 causeways (figs. 4-8) in the bog, clustering upstream where the river narrows. In 2015-16, some nine structures dating from the Migration period to the Early Middle Ages were discovered (figs.10-21, fig. 31). Hard to find and difficult to excavate (figs. 22-23, fig. 29). In 2017, limited parts of several deep-lying, peat-covered Neolithic causeways were excavated non-invasively in the northern part of the complex, more than 2 m below the surface. Wood samples from the massive timber construction A-20 were dated to around 2900 BC, the Late Funnel Beaker culture. Other timbers in the same deep strata, although in a water-eroded position, indicated that similar features date from the end of the 4th millennium BC (figs. 24-28). These comprise the earliest timber-built causeways in Denmark to date. A total of five Neolithic causeways, dating from around 3300 BC to 2600 BC, were documented in the limited trench opened so far. Most of the timbers in these structures, primarily alder, had been cut and trimmed with stone axes. Round timbers showing traces of simple joinery were noted in both A-20 and A-25. These were evidently re-used construction or building timbers. The area that remained in a waterlogged condition was left untouched for possible future excavations. The deepest part adjacent to the Neolithic complex holds a rare potential for recovering both structures and artefacts of organic materials. The peat and other sediments constitute a rich basis for environmental research.